Survival Strategies for city Transport (Public transportation) KPUM Public Transportation Driver Number 46, Bandar Setia Village, Percut Sei Tuan Sub-District - Jefris Alfonsus; Mbina Pinem (Universitas Medan Area, 2023)
This research was conducted in Bandar Setia Village in 2021. The population of this study were public transportation drivers who had worked for at least 4 years, had families and lived in Bandar Setia Village, Percut Sei Tuan District, totaling 23 people and who were also samples in the study. The sampling technique uses Total Sampling. Data collection techniques using interview techniques. The data analysis technique used is descriptive qualitative analysis. The results of this study indicate that the condition of the number 46 KPUM public transportation driver in Bandar Setia Village, in terms of income, is that the income of the public transportation driver is still relatively low, namely 86.96% of the public transportation driver has an income of less than Rp. 2,700,000 per month and is under the 2021 Deli Serdang UMK of Rp. 3,118,592. (2) The conditions of the KPUM public transportation drivers number 46 Bandar Setia Village in terms of recent education show that 60.87% of public transportation drivers have high school/equivalent education. (3) The condition of the KPUM public transportation driver number 46 in Bandar Setia Village in terms of children's education shows that 53.66% are still in education. (4) The survival strategy used by the KPUM public transportation driver number 46, Bandar Setia Village, Percut Sei Tuan sub-district, from the Active strategy, Passive strategy, and the most dominant Network strategy is the passive strategy of 57.60%.